CONSOLIDATION AND DEVELOPMENT OF RELATIONS BETWEEN UZBEKISTAN AND BELARUS DURING THE YEARS OF INDEPENDENCE (Conferencea, 2022)
This article is devoted to the establishment of cooperation relations between the Republic of Uzbekistan and the Republic of Belarus. The article provides information about agreements, contracts and agreements that are the basis of cooperation between the two countries. The article also covers the effective activities of the Intergovernmental Commission of Uzbekistan and Belarus.